Implementasi Kebijakan Program Gizi Anak Sekolah Melalui Pendampingan Guru Sekolah Dasar - Gurning, Fitriani Pramita; Nasution, Fauziah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Nutrition education for primary school teachers is currently one of the government's focuses in the School Child Nutrition Programme in fulfilling the nutritional needs of children. This is considering the many cases of stunting or malnutrition in children which will have an impact on the health and intelligence of children later, if this continues continuously it will produce unqualified human resources, therefore it is necessary to increase the role of every aspect that is directly related to children including the role of teachers. To see the difference in knowledge pre and post nutrition education intervention in elementary school teachers. The study used a Mix Methods approach using Saquential Explatory Design through qualitative and quantitative analysis, in this study qualitative data collection was carried out with Focus Group Discussion (FGD) consisting of 12 informants, quantitative data samples used as many as 30 teachers to measure knowledge variables and tested using t-test to get pre and post intervention differences. There is a pre and post difference in the knowledge variable in the good category before the intervention with a value of 0 and after the intervention to 86.6% with a mean of 17.38 and as well as in the knowledge with the category less which before the intervention 100% to 13.4% with a mean value of 22.08%. And attitudes have an average value before 19.54% and after the intervention increased by 25.43%.There is a significant difference between pre and post intervention knowledge and attitudes in elementary school teachers related to nutrition education. Keywords: Primary School Children, Nutrition, Teachers, Policy Implementation, Programme